RESPON GENJER LIMNOCHARIS FLAVA (L.) BUCHENAU. TERHADAP PEMUPUKAN DAN POTENSI GIZINYA UNTUK DIVERSIFIKASI KONSUMSI SAYURAN - Juhaeti, Titi (Research Center for Biology-Indonesian Institute of Sciences, 2013)
The research was carried out to study the effect of fertilizer on the growth (plant height, number of leaf, length and width of leaf, fresh weight) and flower production of velvet leaf ? genjer Limnocharis flava (L.) Buchenau and to analyze nutrient potential i.e. proximate and amino acids in leaves and flowers (including stalk). Seedlings of velvet leaf with 6 leaves were planted and fertilizer treatments were applied in one week after planting. Planting media were mixture of soil:manure:compost (2:1:1). The fertilizer treatments included control, NPK2, NPK4, MU2, MU4, POH2 and POH4. The plants were cultivated until 5 Weeks After Fertilizing (WAF). The results showed that velvet leaf can be successfully cultivated in plastic pot on planting media added with fertilizer. The highest plant growth and flower production were in the MU4 treatment (NPK Mutiara 27-5-5, 4g/plastic pot). Application of starTmik Biofertilizer 4cc/50cc water/plastic pot showed as good performance as the MU4 treatment, however, the dosage and application frequency need to be increased. The proximate analysis on leaves and flowers showed considerably high percentage of crude fibre (1.56% and 1.42%), protein (2.04% and 1.98%) and carbohydrate (3.16% dan 2.98%). Amino acid analysis revealed 9 numbers essensial amino acids and 8 number non essensial amino acids.